Integration of RCCI and CDF Combustion in Conventional Diesel Engine Using CNG-diesel Fuels: An Experimental Study - J. Chhatbar; P. Rajpara; S. Biswas; R. Banerjee (Journal of Applied Fluid Mechanics)
An experimental investigation is carried out on conventional compression ignition engines' combustion, performance, and emission characteristics using Conventional Dual Fuel (CDF) combustion and reactivity-controlled compression ignition (RCCI) combustion strategies. The experiments are performed on a variable-speed production-grade diesel engine converted to a research engine. Comparative combustion analysis shows that RCCI combustion is more stable and shows a consistent ignition delay across all engine speeds. The exhaust gas temperature of RCCI combustion is lower than that of CDF combustion and is in the range of Conventional Diesel Combustion (CDC). CDC shows better brake thermal efficiency (BTE) than CDF and RCCI combustion across all engine speeds, followed by RCCI combustion. The lowest BTE is observed in CDF combustion. Emission results show that RCCI combustion produced significantly lower NOx emissions than CDC at low engine speed without much HC and CO emissions increment. RCCI combustion does not effectively reduce NOx emissions and produces higher HC and CO emissions at high engine speeds. A BTE-NOx trade-off analysis is also carried out, demonstrating the suitability of RCCI combustion at low engine speed. CDC under high engine speed conditions and in the transition region of medium engine speed CDF combustion is more favorable to reduce NOx emission.